1985
DOI: 10.2165/00003088-198510030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies Between Pharmacokinetic Studies of Amitriptyline

Abstract: In this article, studies on the disposition of amitriptyline after administration of a single dose, as well as following long term administration are reviewed. While long term studies showed bias towards a higher mean apparent oral clearance, studies in normal subjects nevertheless indicated a higher apparent oral clearance than that calculated from steady-state concentrations in depressed patients. Methodological issues could account for some of the discrepancies in mean values of the pharmacokinetic paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Fraction bound values obtained using the 96-well dialysis block and the Spectrum apparatus were very similar to each other and consistent with literature values [21][22][23][24][25][26][27][28][29][30] (Table 1). There were minor shifts in fraction bound values between successive experiments that were attributed to intersubject variations in plasma protein concentrations.…”
Section: Validation Of the 96-well Dialysis Apparatussupporting
confidence: 89%
“…Fraction bound values obtained using the 96-well dialysis block and the Spectrum apparatus were very similar to each other and consistent with literature values [21][22][23][24][25][26][27][28][29][30] (Table 1). There were minor shifts in fraction bound values between successive experiments that were attributed to intersubject variations in plasma protein concentrations.…”
Section: Validation Of the 96-well Dialysis Apparatussupporting
confidence: 89%
“…Thus, these in vitro fi ndings suggest that the metabolism of amitriptyline is lower under steady-state conditions as compared with the single-dose situation. This is supported by the fact that the apparent oral clearance is higher in the single-dose case than that under the steady-state situation [32]. Mellstrom and von Bahr [25] also reported that metabolites of amitriptyline reduced the metabolic rate at therapeutic concentrations.…”
Section: Discussionmentioning
confidence: 95%
“…However, at therapeutic total plasma AMI concenrespectively, were appreciable but did not reach statistical significance. NT formation by a fourth, unidentified enzyme trations (0.15-1 mm) [21], CYPs 2C9, 2D6 and the unidentified enzyme were more important. The contribution was suggested by the finding of residual N-demethylase activity in liver microsomes in the combined presence of of the latter isoforms to net NT formation at 'therapeutic levels' varied significantly from liver to liver.…”
Section: Resultsmentioning
confidence: 90%